Dermatome Distributions in Herpes Zoster Patients at Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2012-2014 - Dara Sabrina; Trisiswati Indranarum; Subur Prajitno (Universitas Airlangga, 2026)
Highlights: Various distributions of dermatomes in HZ patients and the correlations between dermatomes and the history of other diseases. There was a correlation between dermatome location and hypertension as a comorbid disease in HZ patients. Abstract Introduction: Herpes zoster (HZ) can occur when the varicella-zoster virus, which infects the spinal nerves and causes dermatomal injury, reactivates in individuals who have previously had varicella and have healed. This study aimed to identify the risk factors and clinical consequences of HZ among patients at the Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2012 to 2014, in order to support the development of improved preventive strategies and reduce the prevalence of HZ. Methods: This retrospective study used the medical records of 138 HZ patients (n=138). This study employed both descriptive and analytical research methods. The Chi-Square and Fisher’s Exact tests were used in the bivariate analysis. The International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 24.0 was used to analyze the results, which were displayed as tables and charts. Results: Of 138 HZ patients, none had complications. Symptoms of HZ, which were more common among females aged 51 to 60 years old, included burning and pain in the left part of the body (40.58%) and the thoracic dermatome (41%). Most efflorescence (37.2%) belonged to grouped vesicles. Most other disease histories were varicella (53.49%). Correlation test results indicated that dermatome location, sex, symptoms, and a history of other diseases were not associated with efflorescence or age (p<0.05). Nonetheless, there was a connection between hypertension and dermatome location (p=0.008 <0.05). Conclusion: Herpes zoster was more common among females aged 51 to 60 years. Symptoms included discomfort and a burning sensation encircling the lesion in the left thoracal dermatomal region. The majority of patients had a prior varicella infection. Hypertension and dermatome location were correlated.